The Role of Fractional Flow Reserve in Interventional Treatment of Multivessel Coronary Artery Disease - Andrii Yu. Gavrylyshyn (Ukrainian Journal of Cardiovascular Surgery, 2022)
Selective coronary angiography (CAG) is an invasive diagnostic method for the assessment of the internal lumen and anatomical features of the coronary artery. This is a routine procedure and the basis for choosing the tactics of management of patients with coronary artery disease (CAD). However, CAG is a two-dimensional imaging, and despite the use of the poly projection imaging, there may be difficulties in assessing of the degree of stenosis (even by experienced operators, especially in 50–70% lesions). Along with multivessel disease (stenostes of 2 or more main coronary arteries with a diameter of more than 2 mm), this may cause difficulties in interpreting the results of the study and choosing further volume of revascularization (the number of treated stenosis). In these cases, it is necessary to use a combination of CAG with additional functional methods for diagnosing the significance of each coronary stenosis and its role in the occurrence of myocardial ischemia.The aim. To analyze the clinical results of stenting with invasive measurement of fractional flow reserve when choosing the volume of revascularization of 50–70% coronary artery stenoses.Materials and methods. The results of interventions in 109 patients treated at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine from 2017 to 2022 with CAD were studied; in these patients, CAG revealed >50–70% multivessel coronary artery disease. They were divided into two groups: fractional reserve group (main group) undergoing stenting of only symptomatic stenosis according to intracoronary physiological examination (n = 52; 47%), and control group (anatomical revascularization, n = 57; 53%) where stenting was determined according to angiography.Conclusion. Interventional treatment of multivessel CAD with fractional flow reserve assessment enables to avoid inappropriate stenting of hemodynamically insignificant stenoses, thus it is possible to optimize treatment tactics of this group of patients (reduce the number of implanted stents).